Foucault–Barker Mask: Nonconventional Schlieren Technique - Cristina M. Gómez-Sarabia; Jorge Ojeda-Castañeda (Optics, 2025)
We present a theoretical framework for designing optical masks, which are useful for implementing nonconventional Schlieren techniques. We revisit the use of effective transfer functions, which emphasize the role of symmetries in the design of coded masks. The proposed technique implements an optical autocorrelation of a mask, which is coded with the Barker sequences. For the same purpose, one can also use masks coded with the pseudorandom sequences. For the sake of completeness, we link our deterministic theoretical framework with a simple statistical model. The proposed technique may be useful for the automatic sensing of phase gradients.